Understanding charged vesicle suspensions as Wigner glasses: dynamical aspects. (21st December 2020) - Porpora, G; Rusciano, F; Guida, V; Greco, F; Pastore, R
Abstract: Suspensions of charged vesicles in water with added salt are widespread in nature and industrial production. Here we investigate, via Brownian dynamics simulations, a model that grasps the key features of these systems, with bidisperse colloidal beads interacting via a hard-core and an electrostatic double layer potential. Our goal is to focus on a set of interaction parameters that is not generic but measured in recent experiments, and relevant for a class of consumer products, such as liquid fabric softeners. On increasing the volume fraction in a range relevant to real formulation, we show that the dynamics become progressively slower and heterogeneous, displaying the typical signatures of an approaching glass transition. On lowering the salt concentration, which corresponds to increasing the strength and range of the electrostatic repulsion, the emergence of glassy dynamics becomes significantly steeper, and, remarkably, occurs at volume fractions well below the hard-sphere glass transition. The volume fraction dependence of the structural relaxation time at different salt concentration is well described through a functional law inspired by a recently proposed model (Krausser et al 2015 Proc. Natl Acad. Sci. USA 112 13762). According to our results, the investigated system may be thought of as a Wigner glass, i.e. a low-density glassy state stabilized by long-range repulsive interactions. Overall, our study suggests that glassy dynamics plays an important role in controlling the stability of these suspensions.